European Union Democracy Aid : Supporting civil society in post-apartheid South Africa. - Fioramonti, Lorenzo (Routledge/GARNET series. Europe in the world., 2010)
Explores the EU's approach toward civil society since the 1990s and its contribution to democratisation from transition to consolidation, and from the quality of democracy to sustainable development.